Strategic Alignment Impacts on Organizational Performance in Indonesian Banking IndustrY - Iman, Nofie; Hartono, Jogiyanto (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2007)
Strategic alignment has attracted the attention of researchers and practitioners for the last 15 years. This paper reports findings from a survey on the impacts of strategic alignment on organizational performance in the Indonesian banking industry. The survey was conducted through internet-based and postal questionnaires sent to selected companies.Structural Equation Modeling (SEM) is utilized to apprehend the strategic alignment concept as an emergent variable derived from the co-variation ofÂ level of business strategy and level of IS/IT strategy. Hence, we explore the role of this emergent concept as a determinant of organizational performance. Analysis of the data reveals a generally positive impact towards the organizational performance.